Pathophyisiology analysis overload nephron protein in the proximal tubule damage in the nephrolithiasis size stones of 0.6-1.0 sm - Rohovyi, Yu. Ye.; Ariychuk, O. I.; Gerush, O. V. (Journal of Education, Health and Sport, 2017)
Nephrolithiasis as the most common urological disorder characterized by frequent early relapses, acquires a social character, because these patients are 30 to 45% of all urological patients, while in Europe the disease is diagnosed in 2% of the population. The study included 40 patients with nephrolithiasis, 10 patients constituted the control group. Set the “hidden” damage to the proximal nephron in the presence of renal stones with a size of 0.6-1.0 cm in the upper third of the ureter, the upper and middle sections of the calyx, which is confirmed by the inhibition of enzymatic fibrinolytic activity of urine, the presence of tubular proteinuria in the absence of inhibition of proximal reabsorption of sodium ions. The link “hidden” damage to the proximal tubule of the degree of overload of the proximal nephron is a protein graphics multicorrelation dependence between the protein concentration of urine, standardized excretion protein and excretion, which are becoming more significant disharmony form towards control in the following sequence: the upper third of the ureter, medium cup, top cup.